The unintended consequences of biotechnology innovation adoption - Cumming, Douglas; Johan, Sofia; Oberst, Christian; Uzuegbunam, Ikenna (Industry & Innovation, 2020)
We conjecture that adoption of agricultural biotech innovation imposes relationship-specific investments that exacerbate hold-up costs between biotech producers and farmers. Moreover, the increasing presence of biotech reduces biodiversity, which is a significant negative externality on food production across farms. As such, increasing biotech has the potential to exacerbate food insecurity. By contrast, certified organic operations have the potential to have the opposite effect. We examine 15 agrarian states in the U.S. and find evidence strongly consistent with these propositions. We discuss implications for policy, practice, and future research.
Number: 10
Keywords: Réservé UdeM; États-Unis